The Concept of Income in Tax Legislation - Medrano Cornejo, Humberto (1974)
This article explores the legal concept of income, focusing on its definition and its implications within the tax legislation. Thus, the author explores two main theories: on the one hand, the source theory establishes that only periodic and lasting income from a specific source is considered as taxable income; on the other hand, the capital gain theory considers as taxable income all benefits received by the taxpayer, regardless of their origin. In this context, the author points out that Peruvian legislation adopts an intermediate formula, which extends the concept of taxable income to certain specific benefits, without going to the extreme of the capital gain theory. He also addresses the challenges in the definition of habitual activities for tax purposes, highlighting the need to establish requirements to qualify a taxpayer as “habitual” due to the lack of a clear definition of “habituality”, which generates problems of interpretation and practical application around what are habitual transactions. Finally, the author details specific examples of profits that are not considered taxable income, which underlines the importance of a clear and precise interpretation in practice.